2013
DOI: 10.1371/journal.pone.0056763
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of 12/15-Lipoxygenase Alters Macrophage and Islet Function in NOD-Alox15null Mice, Leading to Protection against Type 1 Diabetes Development

Abstract: AimsType 1 diabetes (T1D) is characterized by autoimmune depletion of insulin-producing pancreatic beta cells. We showed previously that deletion of the 12/15-lipoxygenase enzyme (12/15-LO, Alox15 gene) in NOD mice leads to nearly 100 percent protection from T1D. In this study, we test the hypothesis that cytokines involved in the IL-12/12/15-LO axis affect both macrophage and islet function, which contributes to the development of T1D.Methods12/15-LO expression was clarified in immune cells by qRT-PCR, and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 39 publications
4
52
0
Order By: Relevance
“…Collectively, these findings suggest that iPLA 2 ␤ deficiency mitigates polarization of macrophages toward an M1 phenotype. (42)(43)(44)(45). Consistent with this, we find that both ALOX-12 ( Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Collectively, these findings suggest that iPLA 2 ␤ deficiency mitigates polarization of macrophages toward an M1 phenotype. (42)(43)(44)(45). Consistent with this, we find that both ALOX-12 ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…12-S-hydroxyeicosatetraenoic acid) and is not detected in healthy islets but is in both T1D and T2D islets (42), is induced to a much higher level in WT macrophages than in iPLA 2 ␤-deficient macrophages. The importance of 12-LO in promoting macrophage recruitment and activation and causing detrimental effects on islet function and ␤-cell mass is supported by the reports that deletion of 12-LO protects against T1D development (44,45). Our findings, therefore, suggest that iPLA 2 ␤ activation, in addition to skewing macrophage polarization toward M1, may also preserve functionality of downstream lipidmetabolizing enzymes.…”
Section: Discussionsupporting
confidence: 80%
“…Review of 12-lipoxygenase and links to biological systems highlights the important role of 12-lipoxygenase in the development of type 1 diabetes [11,15,17,23,33,34]. Studies of mouse models with transgenic deletion of 12-lipoxygenase suggest that activity of the 12-lipoxygenase enzyme strongly associates with beta cell dysfunction [17,19,33].…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of 12-lipoxygenase protects mice against hyperglycaemia induced with low dose streptozotocin. In the NOD mouse, 12-lipoxygenase deletion confers a near complete protection against type 1 diabetes and also reduces immune cell activation [17,23]. Interestingly, two independent groups have shown that 12-lipoxygenase activation also participates in high-fat-induced insulin resistance and adipose tissue inflammation [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation